Three-Dimensional Finite Element Evaluations of H-Steel Beams Strengthened with Various Types of Steel Stiffeners - Atshan, Ali F.; Radi, Mohammed A.; Kadhum, Ali Kifah; Assi, Malik H.; Hacheem, Zuhair Abd; Taresh, Noor S. (Salehan Institute of Higher Education, 2025)
Three-dimensional finite element analyses were carried out to assess the impact of various types of lateral stiffeners on the response of steel beams. Hot-rolled simply supported H-steel beams were modeled in Abaqus and strengthened with centrally located vertical, V-shaped, inverted V-shaped, single X-shaped, or doubled X-shaped stiffeners. All these stiffeners possess a similar quantity of steel by varying the length and thickness of the stiffeners. The behavior of beams was studied in the elastic phase, hardening phase, necking phase, and failure. The yield stress, ultimate load, deflection value, and hardening in the three phases were also examined. It has been found that the findings indicate that altering the configuration of the stiffener, while maintaining its location and steel volume, can influence the response of the strengthened beam either favorably or adversely. Two stiffeners raised the yield load by 9.6%, the ultimate load by 10.8%, and elastic storage energy by 70% above the reference beam. One kind of stiffener increases in the plastic region, two types drop somewhat, and two others decrease significantly. The necking region shows a rise of 237% in one threshold and 36% to 90% for the other beams compared to the reference beam. Furthermore, the software provides a definitive indication of the kind of stiffener and the degree of its advantage, while simultaneously revealing the type of stiffener that is not advantageous.